STRATEGI PENGEMBANGAN PRODUK UNGGULAN KHAS MERU BETIRI - Eka Nur Jannah; Luh Putu Suciati (UPT Penerbitan Universitas Jember, 2018)
The distinctive superior product of Meru Betiri is a potential product that has competitiveness and is market oriented by utilizing abundant and diverse non-timber forest products (fruit plants and medicinal plants) in the Meru Betiri National Park area. Wonoasri Village, Tempurejo Subdistrict, Jember Regency as one of the buffer villages of the Meru Betiri National Park area has several regional special products through the Joint Business Group formed by the community as banana processing into